Hubungan antara Adab dan Ilmu dalam Dasar-Dasar Pendidikan Islam - Millati Qanitatin; Abdul Khobir; Naisya Maulana Aprilia Rimbani; Muhammad Hilmi Mahfuzh (Yayasan Al-Afif, 2025)
The fundamental relationship between adab and knowledge in the epistemology of Islamic education can be examined through the thoughts of Imam al-Ghazali and Syed Muhammad Naquib al-Attas. Both emphasize that adab is an epistemological foundation that determines the quality of knowledge, not merely a matter of ethical behavior. Adab functions to direct intention, preserve the purity of the heart, and ensure that knowledge is acquired and practiced correctly so that it does not lead to moral or social corruption. Their concept of knowledge shows that knowledge in Islam has complementary spiritual and rational dimensions. Knowledge is understood as a divine light that guides humans toward truth, as well as an intellectual process that must be guided by moral values. Thus, the relationship between adab and knowledge is cyclical: adab prepares the soul to receive knowledge, and knowledge strengthens adab through proper understanding and application. In the context of modern education, this study asserts that moral crises—such as character degradation and the misuse of knowledge—stem from separating knowledge from adab. Therefore, integrating adab and knowledge must be reintroduced into Islamic educational curricula through a holistic approach that unites knowledge, spirituality, and character formation. Such integration offers a conceptual solution to contemporary educational challenges in the digital era and strengthens the aims of Islamic education in shaping knowledgeable and well-mannered individuals.